Effects of Sowing Date and Cutting Management on the Grain and Fodder Yield of Barleyeffects of Sowing Date and Cutting Management on the Grain and Fodder Yield of Barley: Effects of date of seed sowing and cutting management of barley (Bangladesh Journal of Agriculture, 2024)
Cereal crops need to be grown for dual purpose to overcome continuous food and feed shortage. Sowing date and cutting management both are important to obtain the balanced fodder and grain simultaneously. To address the issue, the field experiment was conducted at agronomy field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to find out the effect of optimum sowing date and cutting management on the plant growth, green fodder and grain yield of barley. Five sowing times viz., 30 October, 15 November, 30 November, 15 December and 30 December and four cutting management viz., uncut, cutting at Zadoks growth stage, ZGS 19, cutting at ZGS29 and ZGS31 were used. Results of the present study revealed that early sowing time, 30 October gave significantly higher plant height, dry matter accumulation, effective tiller, fertile spikelet, spike length, 1000-grain weight, grain yield, straw yield, biological yield and green fodder yield under both uncut (control) and cut conditions. Cutting of barley for green fodder had reduced significantly all growth parameters, yield attributes and yield compared to uncut barley. Among cutting schedules, minimum and maximum reduction in growth parameters, yield attributes and yield were recorded with cutting of fodder at ZGS19 (vegetative growth stage) and ZGS31 (stem elongation stage), respectively compared to uncut. However, cutting of barley for fodder purpose at ZGS29 (tillering stage) was found in a balance between green fodder and grain yield simultaneously. Therefore, the study suggested that early sowing (30 October) can compensate the reduction in barley yield due to cutting for fodder purpose and cutting at maximum tillering stage (ZGS29) can balance having optimum grain and green fodder simultaneously.Bangladesh J. Agri. 2024, 49(1): 10-18